2004
DOI: 10.1097/01.ccm.0000119425.04364.cf
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in 137 pediatric cardiac intensive care unit patients managed with extracorporeal membrane oxygenation*

Abstract: In a series of 137 patients managed with ECMO in a pediatric cardiac intensive care unit, survival to hospital discharge was 39%. In postoperative patients only, mortality risk was increased in males, patients <1 month old, patients with a longer duration of mechanical ventilation before initiation of ECMO, and patients who developed renal or hepatic failure while on ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
144
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(159 citation statements)
references
References 25 publications
12
144
3
Order By: Relevance
“…In a previous study, we identified MOF as an independent predictor of fatal outcome in patients with severe heart failure. 8) Morris, et al 9) also reported that development of renal or hepatic dysfunction while patients were on PCPS was a factor associated with an increased probability of mortality in postoperative patients requiring PCPS. Hoskote, et al 10) found that multiple organ system failure was a significant risk factor for poor outcome among the nonsurvivors receiving PCPS after surgery in functional single ventricle patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we identified MOF as an independent predictor of fatal outcome in patients with severe heart failure. 8) Morris, et al 9) also reported that development of renal or hepatic dysfunction while patients were on PCPS was a factor associated with an increased probability of mortality in postoperative patients requiring PCPS. Hoskote, et al 10) found that multiple organ system failure was a significant risk factor for poor outcome among the nonsurvivors receiving PCPS after surgery in functional single ventricle patients.…”
Section: Discussionmentioning
confidence: 99%
“…In older patients, survival was better, 47% to 49% in patients 31 days to 1 year of age and 58% to 59% December 17, 2013 in patients 1 to 16 years of age, and is consistent with large single-center experiences. 494,495 Like CPB, ECMO exposes the blood to a large surface area of foreign material and would result in thrombus formation if not for the use of anticoagulation. Bleeding complications are common, and despite anticoagulation, thrombotic and thromboembolic complications are also common on ECMO.…”
Section: Anticoagulation For Cardiac Ecmo In Children With Chdmentioning
confidence: 99%
“…[20] Many factors including baseline ECMO clinical status, diagnosis, cardiac surgical procedures, timing of initiation of ECMO and ECMO-related factors may affect outcomes for postcardiotomy patients supported with ECMO. The risk factors associated with mortality in children who were supported with ECMO after cardiac surgery were described by Morris et al [21] These risk factors were age below one month, male gender, longer duration of mechanical ventilation before support, and development of renal or hepatic dysfunction while on support. However, functional cardiac physiology (univentricular or biventricular), ECMO indications, and duration of ECMO were not found to be associated with an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%